Contemporary Time Trends in Use of Antiplatelet Agents Among Patients with Acute Coronary Syndrome and Comorbid Diabetes Mellitus or Chronic Kidney Disease. Issue 10 (19th September 2017) - Desai, Rishi J.; Spoendlin, Julia; Mogun, Helen; Gagne, Joshua J.
Abstract : Study Objective: To describe contemporary trends of P2Y12 inhibitor use in patients with acute coronary syndrome (ACS) and comorbid diabetes mellitus (DM) and/or chronic kidney disease (CKD) who have a higher risk of recurring ACS and may benefit from treatment with higher efficacy third‐generation agents (prasugrel and ticagrelor). Design: Observational cohort study. Setting: A large U.S. commercial insurance program (2009–2015). Patients: P2Y12 inhibitor initiated within 2 weeks after an ACS event. Measurements and Main Results: We identified 98, 649 P2Y12 inhibitor initiators, of whom 24.5% had comorbid DM (no CKD), 10.5% had CKD (no DM), and 12.6% had DM and CKD. Overall, 85.2% of patients initiated clopidogrel, followed by prasugrel (11.6%) and ticagrelor (3.2%). Prasugrel use decreased over time irrespective of preexisting DM and/or CKD; ticagrelor use increased. In logistic regression models accounting for patient demographics and clinical covariates, preexisting DM alone was not associated with prasugrel or ticagrelor versus clopidogrel treatment initiation; however, having CKD with or without DM significantly reduced the likelihood of receiving prasugrel versus clopidogrel (odds ratio [OR] 0.81, 95% confidence interval [CI] 0.74–0.88 for CKD alone; OR 0.91, 95% CI 0.83–0.98 for DM and CKD). Comorbid DM and CKD reduced the odds of initiating ticagrelor versus clopidogrel (OR 0.80, 95% CI 0.70–0.92). Principal Conclusions: We observed lower or similar use of prasugrel and ticagrelor compared with clopidogrel in patients with ACS and comorbid DM and/or CKD. Given the potential for worse clinical outcomes with clopidogrel in these patients, our findings highlight the need to investigate the implications of these trends on recurrent ACS and bleeding events.